2022
DOI: 10.1101/2022.01.25.476955
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Transient RNA structures cause aberrant influenza virus replication and innate immune activation

Abstract: During infection, the influenza A virus RNA polymerase produces both full-length and aberrant RNA molecules, such as defective viral genomes (DVG) and mini viral RNAs (mvRNA). Subsequent innate immune activation involves the binding of host pathogen receptor retinoic acid-inducible gene I (RIG-I) to viral RNAs. However, not all influenza A virus RNAs are strong RIG-I agonists. Here we show that potent innate immune activation by mvRNAs is determined by transient RNA structures, called template loops (t-loop) t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
0
1
0
Order By: Relevance
“…In vitro incubations of purified IAV RdRp at different temperatures showed that the dissociation rate of the RdRp is higher on the cRNA template than on the vRNA template, providing a putative molecular explanation for the reduced viral replication ( 48 ). Temperature may also affect the interaction of the IAV RdRp with secondary RNA structures in the viral RNA template, as illustrated by a recent study which showed that RNA duplexes can stall the RdRp and these structures may be less stable at higher temperatures ( 90 ) ( Fig. 1A ).…”
Section: Temperature Impact On Virus Replication Transcription and Rn...mentioning
confidence: 99%
“…In vitro incubations of purified IAV RdRp at different temperatures showed that the dissociation rate of the RdRp is higher on the cRNA template than on the vRNA template, providing a putative molecular explanation for the reduced viral replication ( 48 ). Temperature may also affect the interaction of the IAV RdRp with secondary RNA structures in the viral RNA template, as illustrated by a recent study which showed that RNA duplexes can stall the RdRp and these structures may be less stable at higher temperatures ( 90 ) ( Fig. 1A ).…”
Section: Temperature Impact On Virus Replication Transcription and Rn...mentioning
confidence: 99%